Topographic patterns in the phylogenetic structure of temperate forests on steep mountainous terrain - Kitagawa, Ryo; Mimura, Makiko; Mori, Akira S.; Sakai, Akiko (AoB plants, 2015)
In this study, we tested the topographic trends of measurements of phylogenetic community structure in a catchment covered by temperate forests with complex relief in Japan. We found that phylogenetic structure changed with increasing slope inclination, change of slope aspect from south to north, and decreasing soil depth. Our results suggested that environmental filtering caused by steep topography tended to restrict phylogenetic community composition at relatively stressful sites. On the other hand, species interaction functioned more strongly at relatively stress-free sites. Abstract In rugged terrain subject to active geomorphological processes, the species composition of forest communities changes along topographic gradients over short distances. However, the phylogenetic structure of forests on rugged terrain has rarely been examined. Understanding such structures provides insight into community assembly rules dependent on local environmental conditions. To this end, we tested the topographic trends of measurements of phylogenetic community structure [net relatedness index (NRI) and nearest taxon index] in a catchment covered by temperate forests with complex relief in Japan. We found that phylogenetic structure changed from over-dispersion to clustering with increasing slope inclination, change of slope aspect from south to north and decreasing soil depth. This result suggested that environmental filtering tended to restrict community composition at relatively stressful sites, whereas species interaction functioned more strongly at relatively stress-free sites. Relatively stressful sites were characterized by early-successional species that tended to assemble in certain phylogenetic clades, whereas highly competitive late-successional species associated with lower NRI at relatively stress-free sites. However, despite this significant topographic tendency, phylogenetic community structures were not statistically different from random assumptions in most plots. This obscuration of the phylogenetic structures at the plot level could be interpreted as species adapting to disturbances because they were abundant in this catchment. Accordingly, we suggest that a stochastic process was also important for this community at the plot level, although biotic and abiotic environmental filtering controlled the vegetation structure in the catchment, where disturbances occur frequently because of geomorphological mountain denudation processes owing to active crustal movements and abundant rainfall.